Successful pregnancy in double factor infertility: Sperm in vitro culture by modified testicular fine-needle aspiration. Issue 3 (August 2019) - Cito, Gianmartin; Coccia, Maria Elisabetta; Bertocci, Francesco; Picone, Rita; Cocci, Andrea; Fucci, Rossella; Basile, Valentina; Micelli, Elisabetta; Criscuoli, Luciana; Serni, Sergio; Carini, Marco; Natali, Alessandro
Introduction: Infertility may depend up to 27% of couples on both partners. In patients with obstructive azoospermia, testicular fine-needle aspiration represents a good option to retrieve spermatozoa, in order to perform an assisted reproductive treatment. In vitro maturation of testicular spermatozoa could be the better choice of treatment in view of the increased motility, improving fertilization and pregnancy rates. Case description: A 34-year-old azoospermic man and his 33-year-old partner referred for treatment of simultaneous male and female infertility factor. The woman presented a diminished ovarian reserve, with serum follicle stimulating hormone value of 27.15 IU/L. The man underwent trans-rectal and testicular ultrasounds that detected the congenital absence of proximal vas deferens on the right side and the absence of seminal vesicle and distal vas deferens on the left side. We proposed a chance to have their own biological child. The man underwent modified testicular fine-needle aspiration using a 18-gauge butterfly needle. Sperm retrieval was successful with 0.001 × 10 6 spermatozoa/mL and absence of motility. Testicular sperm suspension was cultured for 24 h to identify sperm viability, achieving 10% of sperm motility. Two metaphase II oocytes were retrieved and processed with intracytoplasmic sperm injection. Clinical pregnancy with live birth was obtained. Conclusion: Performing modified testicular fine-needle aspiration increases successful sperm retrieval. Testicular sperm in vitro culture for 24 h proved to be a real and practical technique to increase sperm motility, in order to select mature and viable spermatozoa and improve successful intracytoplasmic sperm injection outcomes.